1992
DOI: 10.1080/02724936.1992.11747545
|View full text |Cite
|
Sign up to set email alerts
|

Limited impact of a targeted food supplementation programme in Bangladeshi urban slum children

Abstract: An energy-dense supplementary food, together with nutrition education, was given to a group of moderately malnourished children aged 6-12 months in a poor slum community of urban Bangladesh. An age- and sex-matched control group received only nutrition education. Both groups were followed monthly with respect to weight gain and morbidity. The purpose of the study was to assess the differential impact of a targeted supplementary feeding programme with nutrition education and a nutrition education programme alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Across the papers, there was an inference that the type of food product provided is important. The study by Fauveau et al suggested that the lack of iron and zinc in the supplementary food was the reason for the limited longer term effect of the supplement (Fauveau et al, ). Additionally, Christian et al found consistent anthropometric benefits (WHZ and HAZ) of a soy‐based RUSF as well as multiple benefits of the chickpea‐based RUSF.…”
Section: Resultsmentioning
confidence: 99%
“…Across the papers, there was an inference that the type of food product provided is important. The study by Fauveau et al suggested that the lack of iron and zinc in the supplementary food was the reason for the limited longer term effect of the supplement (Fauveau et al, ). Additionally, Christian et al found consistent anthropometric benefits (WHZ and HAZ) of a soy‐based RUSF as well as multiple benefits of the chickpea‐based RUSF.…”
Section: Resultsmentioning
confidence: 99%
“…Fauveau [51] compared education on appropriate complimentary feeding to education plus supplementary feeding in children aged 6-12 months. The supplementary food package contained rice, wheat, lentil power and cooking oil.…”
Section: Resultsmentioning
confidence: 99%
“…Infants living in a variety of settings commonly consume inadequate non-breast milk foods or are weaned onto solid foods rather late, with measurable negative impacts on growth and survival. Close observations of the weaning process in modern peasant populations suggest that patterns of weaning are not simply influenced by availability A. STARCHY FOODS taro(l) "cereal" (2) acorn mush (1) yams(l) bread (2) arrowroot flour (1) bananas rice meal (1) bread (1) corn gricldlecake (1) sago briquettes(I) corn mazamorra (1) millet (1) "cake" (1) B. STARCHY SEMI-SOLIDS rice warmed in milk (1) millet gruel (1) maize gruel(l) rye gruel (1) oat soup (1) C. ANIMAL PRODUCTS meat (8) animal milk (11) fish (2) [cow's (5); goat's (5); sheep's (1); reindeer (2)] bone (2) cheese (1), clarified butter/ghee (3) fat (2) meat (4) "soup" (2) broth (1) fat (2) eggs (1) D. NON-STARCHY FRUITS AND VEGETABLES berries (2) "fruit" (1) nuts (1) roots (1) beans (1) E. BEVERAGES coffee (1), tea (1) meat (2) fish (2) seaweed (1) coconut milk (1) pandanus juice (1) water of weaning foods (Almedom and de Waal 1990;el-Bushra et al 1994;Fauveau et al 1992;Igbedioh and Aderiye 1992;Igbedioh et al 1996;Uwaegbute 1991).…”
Section: Other Factors Influencing Weaning Agementioning
confidence: 99%